Management Accounting: A Catalyst for Organizational Success in the 21st Century - Tarigan, Krisnawati (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
Management Accounting has a central role in supporting the success of holistic organizations in the 21st Century era. Through a qualitative descriptive approach, this research aims to investigate the contribution of management accounting beyond the financial aspect, explore the relationship between an organization's ability to adapt and the contribution of management accounting, and assess the importance of management accounting reports and information in assessing and assessing organizational value added. Research data was obtained from various research results and previous studies that are relevant to the focus of this research. Data processing is carried out carefully to obtain in-depth insights. The results of this research then found that management accounting is not just a financial recording tool, but also a strategy guide that helps organizations go beyond traditional boundaries. The adoption of information technology, the use of big data, and system integration are crucial elements in increasing management accounting efficiency. The role of holistic management accounting includes non-financial aspects, such as the desires and added value of stakeholders.